Applicable Law to matrimonial property regimes. Some issues concerning transitional rules - Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The present work deals with the law applicable to the matrimonial property regimes and transitional rules. The judgement rendered by the court of appeal of Barcelona on July 30th 2019 in examined. The husband’s nationality as a connecting factor is also studied and proves to be discriminatory and non compatible with the Spanish Constitution. In this scenario, the theory of Drittwirkung shows that the Spanish conflict rules are obviously subject to the Spanish Constitution. A distinction is made between marriages concluded before December 29, 1978, those celebrated between December 29, 1978 and November 7, 1990, and those carried out subsequently is made. Finally, this work analyses the reasons for an unstoppable rise of the common habitual residence after the marriage as a connecting factor to determine the Law applicable to matrimonial property regimes.
Keywords: law applicable to the matrimonial property regimes; nationality of the husband’s nationality; Drittwirkung; transitional rules of law; habitual residence